Effects of Process Parameters on Tensile Strength of Jute Fiber Reinforced Thermoplastic Composites (Journal of Naval Architecture and Marine Engineering, 2008)
For Environmental concern on synthetic fibers (such as glass, carbon, ceramic fibers, etc.) natural fibers such as flax, hemp, jute, kenaf, etc. are widely used. In this research work, jute fiber reinforced polypropylene matrix composites have been developed by hot compression molding technique with varying process parameters, such as fiber condition (untreated and alkali treated), fiber sizes (1, 2 and 4 mm) and percentages (5%, 10% and 15% by weight). The developed jute fiber reinforced composites were then characterized by tensile test, optical and scanning electron microscopy. The results show that tensile strength increases with increase in the fiber size and fiber percentage; however, after a certain size and percentage, the tensile strength decreases again. Compared to untreated fiber, no significant change in tensile strength has been observed for treated jute fiber reinforcement. Fractographic observation suggests the fracture behavior to be brittle in nature. Keywords: Natural fiber, Jute fiber, Polypropylene, Composite, Tensile strength.  DOI: 10.3329/jname.v3i1.923 Journal of Naval Architecture and Marine Engineering 3(2006) 1-6